2014
DOI: 10.1007/s00787-014-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic multisite pain in adolescent girls and boys with emotional and behavioral problems: the Young-HUNT study

Abstract: The aim of this study was to assess the prevalence of chronic multisite pain with high disability in relation to emotional or behavioral problems and resilience factors in adolescence. A second aim was to investigate if resilience factors could attenuate the associations between psychiatric symptoms and chronic multisite pain. The study was based on a large cross-sectional study carried out in Norway between 2006 and 2008 and included 7,070 adolescents aged 13-19 years. Chronic multisite pain was defined as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 54 publications
9
58
1
Order By: Relevance
“…This finding coincides with Eriksson's theory, which holds that illness-related suffering is experienced as physical pain originating from disease or its treatment and that spiritual pain originates from feelings of being belittled [13]. Some informants told stories about a weakened, powerless body, while others described increased bodily and spiritual pain, both of which are experiences described in other studies as well [29]. Basic symptoms of ADHD posed enormous consequences of suffering, and some participants were so devastated that they recounted thinking about death as a way to avoid the suffering caused by psychiatric disease.…”
Section: Discussionsupporting
confidence: 88%
“…This finding coincides with Eriksson's theory, which holds that illness-related suffering is experienced as physical pain originating from disease or its treatment and that spiritual pain originates from feelings of being belittled [13]. Some informants told stories about a weakened, powerless body, while others described increased bodily and spiritual pain, both of which are experiences described in other studies as well [29]. Basic symptoms of ADHD posed enormous consequences of suffering, and some participants were so devastated that they recounted thinking about death as a way to avoid the suffering caused by psychiatric disease.…”
Section: Discussionsupporting
confidence: 88%
“…Higher prevalence rates for comorbid pain in cohorts with depression and for depression in cohorts with persistent pain are reported than those for the individual conditions alone 8. Furthermore, up to 75% of people who experience mental health problems also experience pain,9 10 and coexistent psychiatric symptoms increase the prevalence of chronic multisite pain 11…”
Section: Introductionmentioning
confidence: 99%
“…A transitional object can also serve as a therapeutic element and resilience building factor when meeting an adolescent with mental distress and pain symptoms. Recent research has shown that various resilience factors attenuate the association between psychiatric symptoms and chronic multi-site pain (32). Our study reveals the importance of the transitional phenomena and attachment theory in terms of both the emotional and psychosocial development of adolescents and also their somatoform symptoms.…”
Section: Discussionmentioning
confidence: 70%